Innovative in vivo rat model for global cerebral hypoxia: a new approach to investigate therapeutic and preventive drugs - Stahlke, Sarah; Frai, Jonas; Busse, Johanna Franziska; Matschke, Veronika; Theiss, Carsten; Weber, Thomas; Herzog-Niescery, Jennifer (Frontiers in Physiology, 2024)
Severe acute global cerebral hypoxia can lead to significant disability in humans. Although different animal models have been described to study hypoxia, there is no endogenous model that considers hypoxia and its effect on the brain as an independent factor. Thus, we developed a minimally invasive rat model, which is based on the non-depolarizing muscle blocking agent rocuronium in anesthetized animals. This drug causes respiratory insufficiency by paralysis of the striated muscles. In this study, 14 rats underwent 12 minutes of hypoxemia with an oxygen saturation of approximately 60 % measured by pulse oximetry; thereafter, animals obtained sugammadex to antagonize rocuronium immediately. Compared to controls (14 rats, anesthesia only), hypoxic animals demonstrated significant morphological alterations in the hippocampus (cell decrease in the CA 1 region) and the cerebellum (Purkinje cell decrease), as well as significant changes in hypoxia markers in blood (Hif2α, Il1β, Tgf1β, Tnfα, S100b, cspg2, NSE), hippocampus (Il1β, Tnfα, S100b, cspg2, NSE), and cerebellum (Hif1α, Tnfα, S100b, cspg2, NSE). Effects were more pronounced in females than in males. Consequently, this model is suitable to induce hypoxemia with consecutive global cerebral hypoxia. As significant morphological and biochemical changes were proven, it can be used to investigate therapeutic and preventive drugs for global cerebral hypoxia.